2019
DOI: 10.1002/cbic.201900448
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Cascade in Pseudomonas that Produces Pyrazine from α‐Amino Acids

Abstract: Pyrazines are widespread chemical compounds that include pheromones and odors. Herein, a novel mechanism used by Pseudomonas fluorescens SBW25 to biosynthesize monocyclic pyrazines is reported. Heterologous expression of the papABC genes that synthesize the natural α‐amino acid 4‐aminophenylalanine (4APhe), together with three adjacent papDEF genes of unknown function, in Escherichia coli resulted in the production of 2,5‐dimethyl‐3,6‐bis(4‐aminobenzyl)pyrazine (DMBAP), which comprised two symmetrical aminoben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In 2018, Turner et al reported a chemo-enzymatic synthesis of substituted pyrazines using an amino transaminase (S-selective, ATA-113, Codexis [24] ) in the presence of a suitable amine donor, which mediated the key amination of the 1,2-diketone precursor to -aminoketones that underwent oxidative dimerization to the final product (Figure 4). [25] In the case of pyrazines, the chirality S. marcescens 3B2 l-threonine → aminoacetone 2,5-dimethylpyrazine 3 3-ethyl-2,5-dimethylpyrazine 5a [31] HqlA NRPS from P. herquei in E. coli l-thyrosine 4,4′-(pyrazine-2,5-diyl-bis(methylene))diphenol 15 [32] ATRed NRPS from X. indica l-phenylalanine 4,4′-(pyrazine-2,5-diyl-bis(methylene))diphenyl [33] SBW25 from P. fluorescens in E. coli 4-aminophenyl alanine 2,5-dimethyl-3,6-bis(4-aminobenzyl)pyrazine 16 [34] B. subtilis l-threonine, d-glucose 2-ethyl-3,5(3,6)-dimethyl pyrazine 5a/b [35] of the amine group is irrelevant for the synthesis of the aromatic heterocycle core. All reactions were carried out at room temperature with isopropyl amine as the amine donor.…”
Section: Enzymatic Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2018, Turner et al reported a chemo-enzymatic synthesis of substituted pyrazines using an amino transaminase (S-selective, ATA-113, Codexis [24] ) in the presence of a suitable amine donor, which mediated the key amination of the 1,2-diketone precursor to -aminoketones that underwent oxidative dimerization to the final product (Figure 4). [25] In the case of pyrazines, the chirality S. marcescens 3B2 l-threonine → aminoacetone 2,5-dimethylpyrazine 3 3-ethyl-2,5-dimethylpyrazine 5a [31] HqlA NRPS from P. herquei in E. coli l-thyrosine 4,4′-(pyrazine-2,5-diyl-bis(methylene))diphenol 15 [32] ATRed NRPS from X. indica l-phenylalanine 4,4′-(pyrazine-2,5-diyl-bis(methylene))diphenyl [33] SBW25 from P. fluorescens in E. coli 4-aminophenyl alanine 2,5-dimethyl-3,6-bis(4-aminobenzyl)pyrazine 16 [34] B. subtilis l-threonine, d-glucose 2-ethyl-3,5(3,6)-dimethyl pyrazine 5a/b [35] of the amine group is irrelevant for the synthesis of the aromatic heterocycle core. All reactions were carried out at room temperature with isopropyl amine as the amine donor.…”
Section: Enzymatic Approachmentioning
confidence: 99%
“…The novel biosynthetic gene cluster comprised of 4-aminophenylalanine (4APhe) C-acetyltransferase, dihydropyrazine oxidase, and a methyltransferase. [34] A potential industrial strain candidate for 2-ethyl-3,5(3,6)dimethyl pyrazine 5a/b attracted the attention of Zhang et al in 2020 after the isolation of a strain of Bacillus subtilis. They proposed the biosynthetic pathway starting from l-threonine and d-glucose, which were tested by substrate addition and isotope-labeling experiments.…”
Section: Bio-based Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrazines are six-membered heterocyclic compounds with two nitrogen atoms at positions 1 and 4 [14]. Pyrazines are responsible for universally desirable and enjoyable aromas and have been identified in many foods and beverages, particularly as significant volatile components of various nuts, such as peanuts [15], almonds [16], hazelnuts [17] and pecans [18].…”
Section: Introductionmentioning
confidence: 99%
“…The gene sequence included the synthesis of the natural α-amino acid 4-aminophenyl alanine and several other genes for the transformation to non-natural symmetric 2,5-dimethyl-3,6-bis(4-aminobenzyl)pyrazine 16 . The novel biosynthetic gene cluster comprised of 4-aminophenylalanine (4APhe) C-acetyltransferase, dihydropyrazine oxidase, and a methyltransferase [33].…”
Section: Bio-based Synthesismentioning
confidence: 99%